2016
DOI: 10.1155/2016/7893961
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation Index and Hyaluronan Binding Ability in Men from Infertile Couples and Men with Testicular Germ Cell Tumor

Abstract: Objective. To investigate sperm DNA fragmentation and sperm functional maturity in men from infertile couples (IC) and men with testicular germ cell tumor (TGCT). Materials and Methods. Semen samples were collected from 312 IC men and 23 men with TGCT before unilateral orchiectomy and oncological treatment. The sperm chromatin dispersion test was performed to determine DNA fragmentation index (DFI) and the ability of sperm to bind with hyaluronan (HA) was assessed. Results. In comparison with the IC men, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As forother strengths of our study, we wanted to highlighted some facts. Despite that our control group does not contain only men with proven fertile status, our results of SDF assessment were in agreement with other researchers, who have shown that clinically significant threshold to discriminated men with proven fertility from infertile men is approximately 15-20% [18,19,32,33]. Moreover, all participants both normozoospermic volunteers and diagnosed infertile patients came to the same laboratory and the analysis of their semen was carried out in exactly the same way.…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 89%
See 1 more Smart Citation
“…As forother strengths of our study, we wanted to highlighted some facts. Despite that our control group does not contain only men with proven fertile status, our results of SDF assessment were in agreement with other researchers, who have shown that clinically significant threshold to discriminated men with proven fertility from infertile men is approximately 15-20% [18,19,32,33]. Moreover, all participants both normozoospermic volunteers and diagnosed infertile patients came to the same laboratory and the analysis of their semen was carried out in exactly the same way.…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 89%
“…Presented above results are in agreement with data from other authors. Marchlewska et al [19] reported that men from infertile couples had 28.00% spermatozoa with SDF. Majzoub et al [20] revealed significant differences in SDF between infertile and fertile men (mean: 27.60 ± 1.02% vs 15.68 ± 0.92%).…”
Section: Sdf Measured By the Halosperm Test Reflects Male Fertility Pmentioning
confidence: 99%
“…DNA fragmentation is a marker of DNA damage, but also a biomarker of fertility, which is thought to be superior to conventional semen markers in predicting fertility potential. Raised DNA fragmentation, as quantitated by the DNA fragmentation index (DFI), is associated with decreased conception rates and early pregnancy loss . Paoli et al found that after chemotherapy DFI increases significantly 3 months post chemotherapy.…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 99%
“…The regional structure of assets and the number of Islamic banks [18] As we mentioned above, the profitability of Islamic banks is lower than that of traditional banks. Moreover, it is uneven, as Islamic banks in Asian, African and Gulf countries demonstrate relatively higher profitability [19,20].…”
Section: Fig 2 Expected Islamic Assets Globallymentioning
confidence: 99%